Granulocyte Colony Stimulating Factor Ameliorates Hepatic Steatosis Associated with Improvement of Autophagy in Diabetic Rats - Hyun-Woo Joo; Yi-Sun Song; In-Hwa Park; Guang-Yin Shen; Jin-Hee Seong; Na-Kyoung Shin; A-Hyeon Lee; Hyuck Kim; Kyung-Soo Kim (Canadian Journal of Gastroenterology and Hepatology)
Background. We previously reported that the granulocyte colony stimulating factor (G-CSF) ameliorated hepatic steatosis with the enhancement of β-oxidation-related gene expression. However, the mechanisms underlying this process remain unclear. This study aimed to determine whether the improvement of hepatic steatosis by G-CSF was associated with autophagy in a rat model of diabetes. Methods. Eight rats were fed a standard diet, and 16 rats were fed high-fat diet (HFD) for 5 weeks. All HFD-fed rats were then injected with streptozotocin (STZ). One week later, HFD rats injected with STZ were randomly treated with either G-CSF (200 μg/kg/day; diabetes mellitus (DM)/G-CSF) or saline (DM/saline) for 5 consecutive days. Four weeks later, serum biochemical and histology analyses were conducted. The expression of autophagy-associated proteins was determined by Western blotting. The mRNA expression of β-oxidation-related genes was determined by quantitative real-time polymerase chain reaction. HepG2 cells were cultured under high glucose (HG) conditions with G-CSF treatment, followed by Oil Red O staining for quantification of lipids. Results. Histological analysis showed lower lipid accumulation in the DM/G-CSF group than in the DM/saline-treated rats. Protein levels of LC3 and beclin-1 were higher, and those of p62 were lower in the DM/G-CSF rats than in the DM/saline-treated rats. The mRNA expression of β-oxidation-related genes was higher in DM/G-CSF rats than in the DM/saline-treated rats. Quantification of lipid levels in HepG2 cells cultured with HG and G-CSF treatment revealed no significant differences. Conclusions. Our data suggested that G-CSF potentially improves hepatic steatosis and autophagy in the liver of diabetic rats.